Urban Mobility and City Logistics – Trends and Case Study - Rodrigo Rezende Amaral; Ivana Šemanjski; Sidharta Gautama; El-Houssaine Aghezzaf (Promet - Traffic&Transportation, 2018)
Improving urban mobility is crucial to the sustainable development of a city. Well-managed movement of individuals, goods, and services is essential to increase citizens’ welfare, not only by reducing travel times and congestion levels, but also by minimizing air pollution, noise, accidents, etc. To achieve the desired results, the objectives and scope of the optimization efforts have become broader in recent years. Instead of focusing only on the flows and on the network itself, research and projects have connected various areas of economy to traffic management, such as public health and logistic optimization. In this work we discuss the interconnections between urban mobility and city logistics, and present a case study showing how the mobility plan implemented in Ghent (Belgium) in April 2017 affected its logistic system.